2016
DOI: 10.1136/annrheumdis-2016-210198
|View full text |Cite
|
Sign up to set email alerts
|

Thigh muscle MRI in immune-mediated necrotising myopathy: extensive oedema, early muscle damage and role of anti-SRP autoantibodies as a marker of severity

Abstract: Objectives The aims of this study were to define the pattern of muscle involvement in patients with immune-mediated necrotising myopathy (IMNM) relative to those with other inflammatory myopathies and to compare patients with IMNM with different autoantibodies. Methods All Johns Hopkins Myositis Longitudinal Cohort subjects with a thigh MRI (tMRI) who fulfilled criteria for IMNM, dermatomyositis (DM), polymyositis (PM), inclusion body myositis (IBM) or clinically amyopathic DM (CADM) were included in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
103
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 157 publications
(121 citation statements)
references
References 22 publications
8
103
1
9
Order By: Relevance
“…Muscle MRI has only limited value in diagnosing patients with IMNM because it discriminates poorly between patients with IMNM compared to other types of myositis (e.g., dermatomyositis) [40••]. However, muscle MRI may be a useful tool to monitor the evolution of muscle disease over time.…”
Section: Diagnosis and Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…Muscle MRI has only limited value in diagnosing patients with IMNM because it discriminates poorly between patients with IMNM compared to other types of myositis (e.g., dermatomyositis) [40••]. However, muscle MRI may be a useful tool to monitor the evolution of muscle disease over time.…”
Section: Diagnosis and Managementmentioning
confidence: 99%
“…In this regard, we have recently shown that in all types of myositis, including IMNM, fatty replacement begins very early after the onset of the disease. This suggests the possibility that early and intense induction therapy may help to decrease long-term disability in these patients [40••]. …”
Section: Diagnosis and Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, patients have symmetrical and diffuse intramuscular and intrafascial oedema in affected muscles, in anterior, medial and posterior compartments 8. MRI is also useful for localising affected muscles, to guide muscle biopsy and to improve the diagnostic yield.…”
Section: Discussionmentioning
confidence: 99%